Níveis de sódio para codornas japonesas (Coturnix xotunix japonica) nas fases de crecimento e postura - Lima, Raffaella Castro (2009)
With the aim to evaluate the effects of the sodium levels in the growth and laying phases of Japanese quails, we conducted two experiments in which we evaluated the sodium levels of de 0,07%; 0,12%; 0,17%; 0,22%; 0,27% and 0,32%. In the first experiment (growth phase), 480 quails with one day were distributed in a completely randomized design with six treatments of eight replications of ten birds each. According to the results, in the period from 1 to 21 days, there was a linear increase in feed and water intake with the increase in sodium levels and a quadratic effect in the weight gain and feed conversion with optimum sodium levels of 0,23% and 0,21%, respectively. In the period from 21 to 42 days, there was a linear reduction in the weight gain, linear increase in water intake and worse in feed conversion with the increase in sodium in the ration, while feed intake was not affected. In the total period (1 to 42 days of age) with the increase in sodium in the ration, we observed a linear increase in the water intake and in the excreta moisture and a quadratic effect on the digestibility of the dry matter (DCMS), nitrogen (CDN), gross energy (DCEB) and values of apparent metabolizable energy (AME) and apparent corrected (AMEn) with estimated optimum levels of 0,20% for DCMS, 0,27% for CDN and 0,19% for DCEB, AME and AMEn. Moreover, in this experiment we observed that the performance of the laying phase was not influenced significantly by the sodium level supplied to quails in the growth phase. In the second experiment, 288 quails with 16 weeks of age were distributed at random in six treatments with eight replications of six birds each. There was a linear increase in feed intake, in water intake, and in egg weight with the increase in sodium levels and a quadratic effect for egg production, egg mass and feed conversion with optimum sodium levels of 0,23%, 0,24% and 0,23%, respectively. Also, there was a quadratic effect of the sodium levels for percentages the yolk, shell and albumen, obtaining a maximum proportion of albumen and shell and a minimum proportion of yolk with a 0,21% sodium level. There was no significant effect of the sodium levels for the Haugh Units. However, there was a quadratic for specific gravity, with an optimum sodium level of 0.22%. The increase in sodium content did not affect the excreta moisture, but there was a quadratic effect on the digestibility of dry matter (DCMS), nitrogen (CDN), gross energy (DCEB) and values of apparent metabolizable energy (AME) and apparent corrected (AMEn) with estimated optimum levels of 0,24% for CDMS, 0,22% for CDN, 0,21% for CDEB and 0,18% for AME and AMEn. Considering the results, we can recommend that the diets for Japanese quails in the growth phase (1 to 42 days) are formulated with sodium levels between 0,12% and 0,23% and in the production phase with sodium levels between 0,18% and 0,23%